The Robustness of Mental Accounting Across 21 Countries - Priolo, Giulia; Stablum, Federica; Vacondio, Martina; D’Ambrogio, Simone; Caserotti, Marta; Conte, Beatrice; De Roni, Prisca; Du Plooy, Hilda; Grillo, Vivian D; Mastromatteo, Libera Y; Tedaldi, Elisa; Toscano, Filippo; et al. (Journal of Consumer Research, 2026)
First introduced four decades ago, the influential concept of mental accounting—how people mentally organize, evaluate, and track financial activities—posits that consumers often defy traditional economic rationality, treating money as non-fungible across discrete mental accounts. In this research, we present the first large-scale test of the replicability and generalizability of mental accounting effects, using a sample of 5,589 participants from 21 countries. Our results demonstrate that mental accounting effects are replicable, robust, and generalizable. Hierarchical Bayesian meta-analyses revealed a 100% replication rate for all tested scenarios, while unpooled analyses showed a 90.5% replication rate (133/147 effects). Further analysis found that effects observed in higher-income countries may be weaker in lower-income countries. Multidimensional scaling suggested that mental accounting effects vary along three interpretable dimensions that reflect social context (individual vs interactive decisions), decision perspective (deciding for self vs other), and role in price determination (setting vs evaluating prices). Across a diverse population and controlling for multiple factors, we show that consumers make decisions based on mentally-formed accounts that consistently diverge from their objective financial value.